2019
DOI: 10.1186/s12871-019-0771-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrafiltration on extravascular lung water assessed by lung ultrasound in children undergoing cardiac surgery: a randomized prospective study

Abstract: Background Increased lung water and the resultant atelectasis are significant pulmonary complications after cardiopulmonary bypass (CPB) in children undergoing cardiac surgery; these complications are observed after CPB than after anaesthesia alone. Ultrafiltration has been shown to decrease total body water and postoperative blood loss and improve the alveolar to arterial oxygen gradient and pulmonary compliance. This study investigated whether conventional ultrafiltration during CPB in paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
1
3
0
1
Order By: Relevance
“…An increase in B-lines caused worsening oxygenation as measured by PaO 2 /FiO 2 and was associated with longer periods of ventilation. This finding is in agreement with a randomized control trial where LUS was used in congenital heart surgery in which two groups were compared: one with conventional ultrafiltration and the control which did not receive ultrafiltration [ 9 ]. At the end of the surgery, there was a negative correlation with PaO 2 /FiO 2 and LUS score.…”
Section: Discussionsupporting
confidence: 88%
“…An increase in B-lines caused worsening oxygenation as measured by PaO 2 /FiO 2 and was associated with longer periods of ventilation. This finding is in agreement with a randomized control trial where LUS was used in congenital heart surgery in which two groups were compared: one with conventional ultrafiltration and the control which did not receive ultrafiltration [ 9 ]. At the end of the surgery, there was a negative correlation with PaO 2 /FiO 2 and LUS score.…”
Section: Discussionsupporting
confidence: 88%
“…The lung ischemia-reperfusion injury also contributes to lung inflammation [16]. The lung inflammation leads to an increase in pulmonary microvascular permeability and deteriorates lung compliance, increases airway resistance and then aggravates alveolar gas exchange [15,17]. Our study results suggested that prophylactic EPO improved lung compliance, increased gas exchange function, and reduced lung airway pressure.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we found that EPO improved the respiratory mechanics after CPB. During CPB, contact of blood with the CPB circulation tube activates the inflammatory cell releasing lots of inflammatory factors [15]. These inflammatory factors can directly damage endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, is at times not cost-effective for some patients and controversial results in some. 10 Diuretic therapy is a routine part of management of patients with congestive cardiac failure. This is cheap and easily available.…”
Section: Discussionmentioning
confidence: 99%